Desalination of pigment industry wastewater by reverse osmosis using OPM-K membrane - Mohammed Qader Gubari; Haider M. Zwain; Waqed H. Hassan; Mohammadtaghi Vakili; Ali Majdi (Case Studies in Chemical and Environmental Engineering, 2023)
Pigment production plants are among the most polluting industries due to their high-water consumption and complex releases. The current work investigates the removal efficiency of sodium chloride (NaCl), sodium acetate (C2H3NaO2), and acetic acid (CH3COOH), and also the permeate flux of a small-batch OPM-K membrane using reverse osmosis (RO) pilot plant at various concentrations and pressures. At 0.034 M and applied pressure of 30 bar, the results showed that the maximum sodium chloride removal and permeate flow were 93.4% and 8.3 × 10−6 m/s, respectively. When the feed concentration was increased to 0.17 M, the maximum removal efficiency and permeate flow were 88.5% and 4.7 × 10−6 m/s, respectively. In addition, acetic acid has a minimum removal efficiency of 76.2% at 0.062 M and 20 bar applied pressure, while sodium acetate has a minimum permeate flow of 2.8 × 10−6 at 0.061 M and 20 bar. To conclude, the results proved RO membrane's high removal efficiency and permeate flux at low salt concentrations. It should also be noted that RO would be more suitable for the retention of NaCl, C2H3NaO2, and CH3COOH, the three components with the highest concentration in wastewater discharged from pigment production plants.